2017
DOI: 10.1159/000484208
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Inhibits Platelet-Derived Sphingosine-1-Phosphate Induced Endothelial Cell Migration

Abstract: Background: Aspirin plays a crucial role in the prevention of cardiovascular diseases. We previously described that aspirin has effects beyond inhibition of platelet aggregation, as it inhibited thrombin-mediated release of sphingosine-1-phosphate (S1P) from human platelets. S1P is a bioactive lipid with important functions on inflammation and apoptosis. In endothelial cells (EC), S1P is a key regulator of cell migration. In this study, we aimed to analyze the effects of aspirin on platelet-induced EC migratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…S1P is a bioactive sphingolipid metabolite involved in regulating diverse cellular process by binding to a family of five specific G protein-coupled receptors (S1PR 1-5 ), which are present in most tissues but heterogeneous in their expression (2,42,55). It has been shown that S1P is elevated in the airways of individuals with asthma and stimulates ASMC proliferation, migration, and contraction in vitro (1,18,45).…”
Section: Discussionmentioning
confidence: 99%
“…S1P is a bioactive sphingolipid metabolite involved in regulating diverse cellular process by binding to a family of five specific G protein-coupled receptors (S1PR 1-5 ), which are present in most tissues but heterogeneous in their expression (2,42,55). It has been shown that S1P is elevated in the airways of individuals with asthma and stimulates ASMC proliferation, migration, and contraction in vitro (1,18,45).…”
Section: Discussionmentioning
confidence: 99%
“…222 Further exploration has revealed that S1P induces endothelial-cell migration in a concentration-dependent manner, and S1PR1 inhibition abrogates the endothelial-cell migration induced by activated platelets; suppression of S1PR2 or S1PR3 does not induce this effect. 223 Similarly, an indepth assessment of S1P concentration and S1PR expression needs to be performed. SPNS2, a major transporter of S1P in endothelial cells, mediates extracellular pathways of S1P and S1PRs, and influences endothelial-cell migration and angiogenesis.…”
Section: Endothelial Cellsmentioning
confidence: 99%
“…Additionally, hypoxia can enhance the interaction between exogenous S1P and S1PR1 and promote the migration of endothelial cells 222 . Further exploration has revealed that S1P induces endothelial‐cell migration in a concentration‐dependent manner, and S1PR1 inhibition abrogates the endothelial‐cell migration induced by activated platelets; suppression of S1PR2 or S1PR3 does not induce this effect 223 . Similarly, an in‐depth assessment of S1P concentration and S1PR expression needs to be performed.…”
Section: The Role Of the S1p Axis In Metabolic‐related Diseasesmentioning
confidence: 99%
“…Erythrocytes and endothelial cells seem to be the main sources of S1P in plasma; however, platelets also express abundant amounts of S1P [32], and during inflammation and vascular damage, platelets become activated and locally release high levels of S1P [32]. It is noteworthy that these platelet-mediated endothelial protective processes are inhibited by aspirin and NSAIDs, often used to relieve symptoms of infections [33][34][35][36]. Especially worrisome in this regard is the fact that the increase in T1D incidence is paralleled by the increased use of these medications and the observation that the use of NSAIDs is especially frequent in countries with a high incidence of T1D, such as Sweden and Finland [37][38][39].…”
Section: The Vascular Bed Of the Islets As A Hereto-neglected "Locus mentioning
confidence: 99%